2006
DOI: 10.1289/ehp.8959
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Workers Exposed to Toluene and Noise

Abstract: In this study we investigated the risk of hearing loss among workers exposed to both toluene and noise. We recruited 58 workers at an adhesive materials manufacturing plant who were exposured to both toluene and noise [78.6–87.1 A-weighted decibels; dB(A)], 58 workers exposed to noise only [83.5–90.1 dB(A)], and 58 administrative clerks [67.9–72.6 dB(A)] at the same company. We interviewed participants to obtain sociodemographic and employment information and performed physical examinations, including pure-ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 16 publications
3
71
2
14
Order By: Relevance
“…Accepting hippuric acid as a marker of toluene exposure and comparing the levels of hippuric acid for each study, 0.84 g/g creatinine for the present study vs. 2.3 g/g creatinine (BEI 1.6 g/g creatinine) for the Morata et al study, which means exceeding the BEI for more than 43%, the different prevalences of bilateral hearing loss, 36% in the present study vs. 49% in the Morata et al sample and the problem of significance vs. insignificance of the hippuric acid concentration lose their contrariness. When comparing our results to those of Chang et al [4], several shortcomings and curious points may be noted in the results of the second study:…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…Accepting hippuric acid as a marker of toluene exposure and comparing the levels of hippuric acid for each study, 0.84 g/g creatinine for the present study vs. 2.3 g/g creatinine (BEI 1.6 g/g creatinine) for the Morata et al study, which means exceeding the BEI for more than 43%, the different prevalences of bilateral hearing loss, 36% in the present study vs. 49% in the Morata et al sample and the problem of significance vs. insignificance of the hippuric acid concentration lose their contrariness. When comparing our results to those of Chang et al [4], several shortcomings and curious points may be noted in the results of the second study:…”
Section: Resultscontrasting
confidence: 60%
“…The concentration of toluene in ambient air was not found to be significantly associated with hearing loss and no significant associations with hearing loss were noted for the other solvents or noise. In 2006, Chang et al reported odds ratios of at least 104 for high frequency hearing loss > 25 dB after combined exposure to toluene and noise in adhesive manufacturing [toluene in ambient air: 33/107/164 ppm, noise: 83-84 dB(A)] [4]. The results in humans with occupational exposures seem to support the hypothesis of a combined effect of toluene and noise.…”
Section: Problemmentioning
confidence: 94%
“…The synergistic effect of noise and drugs is well established (e.g., Dayal et al 1971;Jauhiainen et al 1972;Eddy and Morgan 1976;Hawkins et al 1976;Vernon et al 1977;Bombard et al 2005), along with the interaction of various industrial chemicals and noise (e.g., Barregard and Axelsson 1984;Fechter et al 2002;Morata et al 2002;Schaper et al 2003;Chang et al 2006). Thus, in combination with the lack of any effect on auditory function of NRTIs alone, the above findings provide a convincing demonstration of a noise/NRTI synergistic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and epidemiological studies confirmed an association between exposure to solvents (styrene, toluene, xylenes, solvent mixtures, and jet fuels) in the workplace and increased prevalence of hearing loss, as well as poor hearing thresholds beyond the traditional 4 kHz noise-related audiometric notch. [83][84][85][86][87][88][89][90][91][92] For an extensive review of human studies, see Johnson and Morata 93 (available online at https:// gupea.ub.gu.se/handle/2077/23240).…”
Section: Co-exposurementioning
confidence: 99%